STRATEGY ANALYSIS OF THE NATIONAL UNIT AND POLITICAL AGENCY OF ETHICS AND POLITICAL CULTURE EDUCATION - Tuswoyo , Tuswoyo; Ndruru, Eka Prasetia (International Peneliti Ekonomi, Sosial dan Teknologi, 2020)
The background of this research is about ethics education and political culture discussing moral issues and political cultural background in DKI Jakarta Province. The National United and Politics Board has programs as referred to in Article 27 clause (1) of the Governor of OKI Jakarta Regulation, namely: Politics and Democracy Division has the task of carrying out the guidance and development of political culture education, democracy, and facilitation of political institutions. This research uses a qualitative approach. The focus of this research is on the Policy Strategy of the National United and Politics Board consisting of: Strategies, constraints or impediments, and solutions. From the research results, it was known that the implementation of ethics education and political culture aimed to provide understanding to the public on political ethics and culture as the embodiment of national and state life, carried out through seminars, community organizations, students, and workshops. Referring to the Minister of Home Affairs Regulation Number 36 of 2010 concerning Guidelines for Facilitating the Implementation of Political Education that, the objectives of implementing political education is the increased awareness of the rights and obligations of the community in the life of society, nation, and state; increased independence, maturity, and achievement in the administration of political and state life.